Peran Orangtua Tunggal terhadap Perkembangan Anak Down Syndrome (Studi pada Single Mother dan Single Father) - Rila Rahma Mulyani; Rivoni Melati; Rahayu Khoirunnisa (Universitas PGRI SUMATERA BARAT, 2021)
ABSTRACT This research is motivated by the existence of single parents (single mother and single father) who have down syndrome children in nurturing, guiding, and caring for children without being accompanied by a partner. The purpose of this study is to describe the role of single parents on the development of children with down syndrome seen from 1) decision-makers, 2) responsibilities as parents, 3) responsibilities as teachers, and 4) advisors. This research was conducted using qualitative methods. The key informants in this study consisted of two people, one single mother and one single father who had a child with Down syndrome. While the additional informants are three people each from a single parent. The instruments used are interviews and observations. As for the data analysis technique using data reduction, data presentation, and drawing conclusions. The results showed that 1) Single parents as decision-makers were seen from single mothers who decided to take care of their children by themselves by providing physical therapy and speech therapy according to the doctor's advice, while single fathers also consulted with doctors to monitor their child's development and asked for help from the eldest child to take care of his sister. 2) The responsibility as a parent of a single mother is shown by sending their children to school to be independent and practicing communication with others as well as actively sharing information with other parents who also have Down syndrome children, while single fathers feel responsible for helping their children adjust by not feeling bad. ashamed to have a child with down syndrome. 3) The responsibility as a teacher of a single mother is shown by assisting children in doing assignments and directing them to be independent in carrying out daily activities, while single fathers do not have much time to accompany children's activities at home because of busywork. 4) The single parent as an advisor is seen from the single mother, namely giving directions slowly to the child in daily activities, while the single father understands the limitations of the child by being patient and accepting the mistakes made by the child. Keyword:Role, Single Mather, Single Father, Down Syndrome ABSTRAK Penelitian ini dilatar belakangi oleh adanya orangtua tunggal (single mother dan single father) yang memiliki anak down sndrome dalam mengasuh, membimbing dan merawat anak tanpa didampingi pasangan. Tujuan penelitian ini untuk mendeskripsikan peran orang tua tunggal terhadap perkembangan anak down syndrome dilihat dari: 1) Pengambil keputusan, 2) Tanggung jawab sebagai orang tua, 3) Tanggung jawab sebagai guru, dan 4) Penasehat. Penelitian ini dilakukan dengan menggunakan metode kualitatif. Informan kunci dalam penelitian ini terdiri dari dua orang yaitu satu single mother dan satu single father yang memiliki anak down syndrome. Sedangkan informan tambahan masing-masing tiga orang dari single parent.Instrumen yang digunakan yaitu wawancara dan observasi.Sedangkan untuk teknik analisis data menggunakan reduksi data, penyajian data, dan penarikan kesimpulan.Hasil penelitian menunjukkan bahwa 1) Orangtua tunggal sebagai pengambil keputusan dilihat dari single mother yaitu memutuskan untuk merawat sendiri anaknya dengan memberikan terapi fisik serta terapi berbicara sesuai saran dokter, sedangkan single father juga berkonsultasi dengan dokter untuk memantau perkembangan anaknya dan meminta bantuan dari anak tertua untuk merawat adiknya.2) Tanggung jawab sebagai orangtua dari single mother ditunjukkan dengan menyekolahkan anak untuk bisa mandiri serta melatih komunikasi dengan orang lain disamping juga aktif berbagi informasi dengan orangtua lain yang juga memiliki anak down syndrome sedangkan single father merasa bertanggung jawab dalam membantu anak menyesuaikan diri dengan tidak merasa malu memiliki anak down syndrome. 3) Tanggung jawab sebagai guru dari single mother ditunjukkan dengan mendampingi anak mengerjakan tugas serta mengarahkan untuk bisa mandiri dalam melakukan aktifitas sehari-hari sedangkan single father kurang memiliki banyak waktu untuk mendampingi kegiatan anak di rumah karena kesibukan bekerja. 4) Orangtua tunggal sebagai penasehat dilihat dari single mother yaitu memberitahu arahan secara perlahan kepada anak dalam kegiatan sehari-hari, sedangkan single father memahami dengan keterbatasan yang dimiliki anak dengan bersabar dan menerima kesalahan yang dilakukan anak. Kata Kunci: Peran, Single Mother, Single Father, Down Syndrome